Cerebral processing of pain in rheumatoid arthritis patients treated with antiTNF-alpha - Wartolowska, K; Schweinhardt, P; Wordsworth, P; Chizh, B; Chessell, I; Tracey, I (2008)
Aim of Investigation: To examine the mechanisms involved in chronic pain and its relief using functional magnetic resonance imaging (fMRI). We were interested in how evoked clinical joint pain processing in rheumatoid arthritis (RA) patients changes after anti-TNF-alpha treatment. Anti-TNF treatment blocks the action of TNF-alpha, a key factor in joint inflammation, suppressing disease activity in severe RA reducing both joint pain and inflammation. Methods: Twenty-one patients with severe RA and due to begin anti-TNF treatment have so far been recruited to the study with full informed consent. We used fMRI to investigate changes in brain activation in response to joint pressure pain and thermal stimulation at a fixed temperature to elicit moderate pain over the course of treatment (i) before the treatment, (ii) 1 month, (iii) 8 months after treatment began. Clinical, psychological and psychophysical data was collected at each time point. Results: Up to now, 10 patients have responded positively to treatment and completed all 3 time points (TP). Clinical and psychobehavioural results Between TP-1 and TP-2 there was a significant decrease in pain ratings, on 11-point numerical rating scale for both pressure (5.1 vs. 3.3 p=0.002) and heat (6.2 vs. 5.1 p=0.004), as well as for daily pain (5.9 vs. 4.3 p=0.004). The difference between the TP-1 and TP-3 was even more significant: for pressure pain ( and daily pain but not more sp for heat pain. There was a significant reduction in disease activity score in 28 joints (DAS 28) and blood inflammatory markers. There was no significant difference in the depression and catastrophising scores for TP-1 vs. TP-2, but they both significantly decreased at TP-3 vs. TP-1. Imaging results: We observed a robust activation in response to both types of painful stimuli. In the pressure pain condition there was a decrease in activation, at TP-2 vs. TP-1 in the left primary sensorimotor cortex, secondary sensory cortex bilaterally and right insula. For TP-3 vs. TP-1 there was a decrease of activation bilaterally in insula and somatosensory cortex. For heat stimulation, there was a bilateral decrease in activation in cingulate, thalamus and striatum for the TP-2 vs. TP-1 but not for the TP-3 vs. TP-1, reflecting perhaps modulation of nociceptive processing as patients recover. Conclusions: We observed a notable reduction in disease activity after 1 month of treatment in clinical, psychological and fMRI data. The observed imaging changes correlated with a reduced noxious input and decreased perceived pain intensity. Acknowledgments: The study was funded by GlaxoSmithKline as a part of an ongoing academic collaboration.